APPLICATION DEVELOPMENT OF ENTITY-RELATIONSHIP DIAGRAM CONVERSION TO LOGICAL SCHEMA OF COLUMN ORIENTED NOSQL - Fauzan Al-Ghifari, Muhammad
With the increasing usage of column-oriented NoSQL, steps that can model the data structure of this technology are needed. Poffo & Mello (2016) have conducted research that discusses the conversion of Entity-Relationship Diagram (ERD) to logical schema of column-oriented NoSQL. Data modelling in NoSQL requires the support of tools or applications, so that in the future it is hoped that the data modelling process on this technology will be faster and more accurate. However, there is currently no application that supports conversion from ERD to logical schema of column-oriented NoSQL. In this research, an application for converting ERD to logical schema of column-oriented NoSQL and conversion of the logical schema to data definition language for column-oriented NoSQL will be developed. The analysis begins with data modeling for the entity-relationship model and the logical model of column-oriented NoSQL. After that, an algorithm is built that performs the conversion from the entity-relationship data model to the logical model of the NoSQL and produces a data definition language in the form of Cassandra Query Language, one of the column-oriented NoSQL. The logical data model and conversion algorithm are built based on the logical schema proposed by Poffo & Mello (2016) Applications development begins with defining the functional requirements of the